2021
DOI: 10.1002/aenm.202101566
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Illumination Photoconductivity Enables Extension of Photo‐Catalysis after Sunset

Abstract: Cloud‐cover‐induced frequent and sharp dips in sunlight as well as diminished solar flux during the evenings of peak energy demand are major challenges in solar energy harvesting. Persistent and memory‐based photocatalysts that efficiently operate under low light fluxes beyond sunset, are a potential solution to address and mitigate these challenges. This review describes examples of persistent photocatalysis systems based on charge injection into multivalent charge storage materials that allow post‐illuminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 136 publications
0
24
0
Order By: Relevance
“…For an n-type semiconductor, the electric field in its surface space-charge region could cause photogenerated electrons to be swept away from the surface and excess photogenerated holes to be swept toward the surface, which subsequently reduces the surface-trapped electron density and increases the surface positive charge . For the h -WO 3 /Bi 2 WO 6 -20-1 sample, however, the localization of photogenerated electrons could reduce W 6+ to W 5+ and generate W 5+ band states below the conduction band edge . Thus, photogenerated electrons could transfer from its valence band into W 5+ band states, which subsequently increases the surface negative charge and causes its SPV signal to move to a less positive direction.…”
Section: Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For an n-type semiconductor, the electric field in its surface space-charge region could cause photogenerated electrons to be swept away from the surface and excess photogenerated holes to be swept toward the surface, which subsequently reduces the surface-trapped electron density and increases the surface positive charge . For the h -WO 3 /Bi 2 WO 6 -20-1 sample, however, the localization of photogenerated electrons could reduce W 6+ to W 5+ and generate W 5+ band states below the conduction band edge . Thus, photogenerated electrons could transfer from its valence band into W 5+ band states, which subsequently increases the surface negative charge and causes its SPV signal to move to a less positive direction.…”
Section: Results and Discussionmentioning
confidence: 99%
“…49 For the h-WO 3 /Bi 2 WO 6 -20-1 sample, however, the localization of photogenerated electrons could reduce W 6+ to W 5+ and generate W 5+ band states below the conduction band edge. 26 Thus, photogenerated electrons could transfer from its valence band into W 5+ band states, which subsequently increases the surface negative charge and causes its SPV signal to move to a less positive direction. Thus, the much weaker SPV signal of the h-WO 3 /Bi 2 WO 6 -20-1 sample indicated that more photo-generated electrons were transferred to W 5+ band states than that of the h-WO 3 sample.…”
Section: Optical Properties and Bandmentioning
confidence: 99%
See 3 more Smart Citations